2004
DOI: 10.1902/jop.2004.75.2.292
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Adhesion on Commercially Pure Titanium and Zirconium Oxide Disks: An In Vivo Human Study

Abstract: Our results demonstrate that zirconium oxide may be a suitable material for manufacturing implant abutments with a low colonization potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
398
6
16

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(434 citation statements)
references
References 29 publications
14
398
6
16
Order By: Relevance
“…The standard deviation of the Ra was large in the RS group and small in the MS group, indicating that the Ra values in the latter group were approximately correct. Shintani (14) reported that plaque adhesion increases on rougher surfaces. In contrast, Bollen et al reported that Ra values less than 0.2 µm do not affect bacterial adhesion (28), and a study by Nascimento et al showed that bacterial adhesion to titanium and zirconium was insensitive to Ra (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard deviation of the Ra was large in the RS group and small in the MS group, indicating that the Ra values in the latter group were approximately correct. Shintani (14) reported that plaque adhesion increases on rougher surfaces. In contrast, Bollen et al reported that Ra values less than 0.2 µm do not affect bacterial adhesion (28), and a study by Nascimento et al showed that bacterial adhesion to titanium and zirconium was insensitive to Ra (29).…”
Section: Discussionmentioning
confidence: 99%
“…The quantity of plaque generated on the surfaces of these materials has varied substantially in clinical trials. However, the surface characteristics of dental materials, as well as the adhesion and generation of biofilms on these surfaces, are rarely reported (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, zirconium is particularly preferred in the front teeth. Zirconia has been proven highly bio-compatible in many studies [3], and the accumulation of bacteria has been reported less than titanium [4]. In this sense, the implant material should provide the needs of the patient mechanical resistance, aesthetic appearance and should have biocompatibility and Osseointegration of dental implant.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The good mechanical properties and biological compatibility of zirconia (zirconium dioxide) have led to its increased use for various dental applications. 7,8 A number of advantages of ceramics over metal abutments have been reported in the literature: less mucosal discoloration, 9 less adhesion of bacteria, 10 very low or no cytotoxicity as measured in vitro human gingival fibroblast, 11 and mucosal attachment to zirconia that is as good as that to titanium, according to an animal study. 12 The three-year results from a randomized controlled clinical trial comparing customized zirconia and titanium abutments showed no difference in outcome from technical, biological, or esthetic points of view.…”
Section: Dislodgement Resistance Of Zirconia Copings Cemented Onto Zimentioning
confidence: 99%